Antibiotics Resistance Pattern of Coliform Bacteria Isolated from Slaughterhouse Wastewater in Jega Town, Kebbi State, Nigeria - Adamu Almustapha Aliero; Namadina Hassan Jega; Ahmad Ibrahim Bagudo; Sahabi Sule Manga; Kabiru Hussaini (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Wastewater is an essential reservoir of pathogenic bacteria, which include resistant strains. This study determined the antibiotics resistance pattern of Coliform bacteria isolated from slaughterhouse wastewater in Jega local government. Five different samples of wastewater from different locations of a slaughterhouse were collected using standard sample collection techniques. Coliform bacteria were isolated using the standard microbiological method. The total bacterial count was determined using plate count agar. Suspected coliforms were identified based on morphological and biochemical tests. Antimicrobial susceptibility testing was carried out using the standard disc diffusion method. The highest bacterial count (8.4x102 CFU/ml) was observed from the wastewater collection point, and the lowest bacterial (1.2x102 CFU/ml) count from the slaughtering point. Three Gram-negative bacteria, Escherichia coli, Pseudomonas aeruginosa, and Enterobacter aerogenes, were identified. Escherichia coli was the most frequently isolated in slaughterhouse wastewater 39 (45.8%). Among the antibiotics tested against isolated bacteria, Septrin was the most resistant antibiotics recorded against E. coli and E. aerogenes with 84.61% and 88.89% resistant, respectively. Pseudomonas aeruginosa was found to show higher resistance to Chloramphenicol and Septrin with 84.21% resistance each. The occurrence of antibiotic-resistant bacteria from slaughterhouse wastewater showed the risks associated with antimicrobial drug resistance transferred from food-producing animals to humans. Management concerns, such as local government health officers and community development officers, should increase the sensitization of slaughterhouse workers by organizing conferences or conducting radio talk to educates these slaughterhouse workers on the treatment of slaughterhouse wastewater and health risk associated with antimicrobial-drug resistance transferred from animals to humans.